1992
DOI: 10.1002/cm.970210202
|View full text |Cite
|
Sign up to set email alerts
|

The role of β1 integrin in spreading and myofibrillogenesis in neonatal rat cardiomyocytes in vitro

Abstract: The influence of the extracellular matrix (ECM) on cell behavior, myofibrillogenesis and cytoarchitecture was investigated in neonatal rat cardiac myocytes in vitro. Cell behavior was examined by analyzing cell spreading on different ECM components under a variety of experimental conditions. Area measurements were made on digitized images of cells grown for various time intervals on fibronectin (FN), laminin (LN), collagens I and III (C I+III), plastic, and bovine serum albumin (BSA). The amount of spreading w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 57 publications
3
42
1
Order By: Relevance
“…Ubiquitination is the first step in non-lysosomal protein degradation (Hershko and Ciechanover, 1992) and we do indeed find an upregulation of ubiquitin expression in dividing cardiomyocytes. While in interphase cardiomyocytes the signal for the ubiquitin antibody is rather weak and mainly associated with the nuclei as reported previously (Hilenski et al, 1992) (Fig. 6B, cells in top left corner of E); once cardiomyocytes enter mitosis, ubiquitin starts to be spread throughout the cytoplasm (Fig.…”
Section: How Is Myofibril Disassembly Regulated?supporting
confidence: 84%
“…Ubiquitination is the first step in non-lysosomal protein degradation (Hershko and Ciechanover, 1992) and we do indeed find an upregulation of ubiquitin expression in dividing cardiomyocytes. While in interphase cardiomyocytes the signal for the ubiquitin antibody is rather weak and mainly associated with the nuclei as reported previously (Hilenski et al, 1992) (Fig. 6B, cells in top left corner of E); once cardiomyocytes enter mitosis, ubiquitin starts to be spread throughout the cytoplasm (Fig.…”
Section: How Is Myofibril Disassembly Regulated?supporting
confidence: 84%
“…For example, Foster et al (1987) have found that a laminin substrate promotes myogenesis in rat skeletal muscle cultures and Hilenski et al (1992) have reported that laminin influences cytoskeletal and myofibrillar organization in vitro in neonatal rat cardiac myocytes. Further, mutations in the genes coding for the alpha-2 chain of two laminin isoforms have been shown to cause a severe form of congenital muscular dystrophy in humans and mice (Kuang et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that ECM components play an important role in assembly and/or maintenance of myocyte cytoarchitecture (Hilenski et al, 1992; Imanaka-Yoshida et al, 1999; Shiraishi et al, 1997). In addition, it has been proposed that focal adhesions might serve as nucleation sites for the assembly of myofibrils (Lin et al, 1989).…”
Section: Cell-ecm Interactions Appear Normal In N-cadherindeficient Mmentioning
confidence: 99%
“…Similar to Ncadherin, β1 integrin is expressed in the developing and mature myocardium (Carver et al, 1994;Terracio et al, 1991). In the presence of anti-β1 integrin antibodies, normal cell spreading and myofibril organization was perturbed in cultured neonatal rat cardiomyocytes (Hilenski et al, 1992). Myocytes derived from β1 integrin double-knockout embryonic stem (ES) cells exhibited altered in vitro differentiation and abnormal sarcomeric architecture (Fassler et al, 1996).…”
mentioning
confidence: 99%